2022
DOI: 10.26803/ijlter.21.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of the GeoGebra Application in Learning Circle Theorems

Abstract: The learning area of circle theorems is one of the most difficult topics in geometry, resulting in low student performance. GeoGebra has been shown in studies to enhance learners' proficiency in circle theorems. However, pre-service teachers' use of GeoGebra is not at the expected level in Eswathini. The adoption of an information system is reliant on its acceptance by individuals. However, little is known regarding pre-service teachers' use of GeoGebra to understand circle theorems. The goal of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…Specifically, when students feel that ChatGPT aligns with their learning values, styles, and needs, they consider the use of ChatGPT as essential and beneficial in their learning, enabling them to complete various learning tasks and better integrate into the learning process. This result not only validates the view that compatibility has a positive impact on task-technology fit [3], but also further confirms that if a system is reasonable, flexible, and comprehensive in terms of technology, people usually find it suitable and practical [82]. Moreover, in line with many studies, when ChatGPT has high compatibility, it helps to enhance students' academic achievements, thus improving the performance impact [81,85], promoting the sustainable development of education.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Specifically, when students feel that ChatGPT aligns with their learning values, styles, and needs, they consider the use of ChatGPT as essential and beneficial in their learning, enabling them to complete various learning tasks and better integrate into the learning process. This result not only validates the view that compatibility has a positive impact on task-technology fit [3], but also further confirms that if a system is reasonable, flexible, and comprehensive in terms of technology, people usually find it suitable and practical [82]. Moreover, in line with many studies, when ChatGPT has high compatibility, it helps to enhance students' academic achievements, thus improving the performance impact [81,85], promoting the sustainable development of education.…”
Section: Discussionsupporting
confidence: 81%
“…Empirical research by Alamri, Almaiah [3] in the context of social networking applications within higher education has shown a positive correlation between compatibility and task-technology fit. According to a study by Philemon, Chibisa [82], the compatibility of the mathematics application software GeoGebra 5.0 had a significant positive impact on task-technology fit. Isaac, Aldholay [35] suggested that performance impact refers to the extent to which information systems can improve work quality, i.e., enhancements in students' academic achievements.…”
Section: Compatibilitymentioning
confidence: 99%
“…Este modelo se basa en la idea de que la percepción de la utilidad y facilidad de uso de una herramienta influyen en la actitud del usuario hacia la misma y su intención de usarla. El modelo TAM ha sido ampliamente utilizado (Pittalis, 2021,Nxumalo et al, 2022,Yeo et al, 2022 en investigaciones sobre TIC, y se ha demostrado que es una herramienta muy útil para comprender la adopción de nuevas tecnologías en diferentes ámbitos, tales como la educación, la salud y los negocios.…”
Section: Introductionunclassified